சிந்தனைத் தளத்தில் சுகுமாரனின் வண்டு குண்டு / Thoughts in Sukumaran's Vandu Kundu - முனைவர் ந. இரஞ்சன் / Dr. N. Ranjan (International Journal of Tamil Language and Literary Studies)
The rhetoric of children’s literature has evolved significantly over time by leading to its formal establishment as a distinct Tamil literary domain. The term "children" traditionally encompasses both small boys and girls; however, in contemporary discourse, there is a prevailing tendency to associate "children" primarily with male children, while referring to female children separately as "girls." This distinction is observed even among academics with advanced degrees, reflecting a broader linguistic and cultural shift. In the field of Tamil literature, most classical and modern works focus on men and women with limited references to boys during the Sangam period. Unlike later developments in Tamil literature, there was no exclusive work dedicated to boys during this era. However, recent years have witnessed renewed efforts to develop children's literature by resulting in the emergence of diverse literary forms aimed at young readers. Among contemporary Tamil writers contributing to this field, Sukumaran is a Tamil writer who focused on writing children's literature. He has gained recognition for his works that centre on children’s perspectives and experiences. This paper examines Sukumaran’s “Vandu Kundu” with a specific focus on the underlying themes and thought processes reflected in the collection. It explores the cognitive and psychological dimensions of children as depicted in Sukumaran’s stories by analyzing how he captures their thoughts, emotions and behaviours. This analysis also employs descriptive, analytical and statistical methods to examine the narrative structure, themes and rhetorical techniques used in “Vandu Kundu”. Furthermore, the study identifies key areas for future research in Tamil children's literature by emphasizing the need for a broader representation of childhood experiences in literary discourse. Through this critical examination, the paper contributes to a deeper understanding of children’s literature as an evolving literary tradition.